Information retrieval in instant messaging platforms using Recurrent Neural Networks Assisting Discussion Forum Users Using Deep Learning - Suorra, Jacob Hagstedt Persson (My University, 2016)
We present a discussion forum assistant based on deep recurrent neural networks (RNNs). The assistant is trained to perform three different tasks when faced with a question from a user. Firstly, to recommend related posts. Secondly, to recommend other users that might be able to help. Thirdly, it recommends other channels in the forum where people may discuss related topics. Our recurrent forum assistant is evaluated experimentally by prediction accuracy for the end–to–end trainable parts, as well as by performing an end-user study. We conclude that the model generalizes well, and is helpful for the users.
Keywords: Data- och informationsvetenskap; Computer and Information Science